La problématisation : une entrée pour examiner et repenser l'apprentissage des élèves en éducation physique et sportive à l'école maternelle - Marine Véjux-Grillot (Nantes Université, 2017)
This article reports on a collaborative approach in three classes of the third year of nursery school. The study brings together preschool teachers and one researcher collaborating on a « forced situation » (Orange, 2010) in collective games. The situation is based on an alternation « action-debate-action » for the pupils. The objective is the pupils problematize from an obstacle encountered in situation in order to surpass it and to transform their motor skills. The ability of nursery pupils to problematize as well as the impact of the problematization activity in the construction of motor learning in physical education are examined in this study.